1993
DOI: 10.1161/01.str.24.12.1850
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of incidentally discovered unruptured aneurysms.

Abstract: Intracranial aneurysms are formed not only at the bifurcation of an artery but also at its branching and bending points. However, an aneurysm located at the bifurcation, such as the anterior communicating artery and the middle cerebral artery, bleeds easily in contrast with lateral aneurysms such as those found at the branching and bending points on the internal carotid artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 28 publications
3
58
1
3
Order By: Relevance
“…It has also been shown that the prevalence of unruptured IA is significantly higher (10.5-13.5%) in a Japanese subgroup with a family history of IA Kojima et al 1998). The prevalence of harboring an IA within the population aged over 30 years is between 3.6 and 6.5% (Ujiie et al 1993;Yamaki et al 1994;Iwamoto et al 1999;Wardlaw and White 2000). Especially in Japan, where a brain assessment system called ''Braindock'' systematically screens patients for incidental aneurysms, the incidence of unruptured IAs seems to be increasing with the continuous evolution of magnetic resonance angiography imaging techniques (Yoshimoto and Mizoi 1997;Morita et al 2005).…”
Section: Pathology Epidemiology and Etiologymentioning
confidence: 99%
“…It has also been shown that the prevalence of unruptured IA is significantly higher (10.5-13.5%) in a Japanese subgroup with a family history of IA Kojima et al 1998). The prevalence of harboring an IA within the population aged over 30 years is between 3.6 and 6.5% (Ujiie et al 1993;Yamaki et al 1994;Iwamoto et al 1999;Wardlaw and White 2000). Especially in Japan, where a brain assessment system called ''Braindock'' systematically screens patients for incidental aneurysms, the incidence of unruptured IAs seems to be increasing with the continuous evolution of magnetic resonance angiography imaging techniques (Yoshimoto and Mizoi 1997;Morita et al 2005).…”
Section: Pathology Epidemiology and Etiologymentioning
confidence: 99%
“…15 A previous study of 44 unruptured aneurysms selected from 1612 patients showed that aneurysms located at bifurcations, especially the anterior communicating artery and the middle cerebral artery, bleed easily compared with those located at the branching and bending points. 16 Therefore, due to the high sensitivity of bifurcation aneurysms to variations of flow pattern and morphology, the hemodynamic parameter EL was used to evaluate the growth and rupture of this type of aneurysm. The aim of this study was to elucidate the relationship between the morphologic parameters of bifurcation aneurysms, including the bifurcation angle configuration; DA ratio; and hemodynamic parameters of EL and abnormal low WSS.…”
mentioning
confidence: 99%
“…The risk of aneurysm is also higher in a blood vessel with unusual flow (12). An aneurysm at bifurcation has a higher risk of rupture because the shock waves are direct systolic (27). This indicates that it is more important to watch the blood stream and the angle between this blood stream and the one that is entering the aneurysm than the angle that anatomically closes the aneurysm in the carrying blood vessel (7,8).…”
Section: Aspect Ratio (Ar)mentioning
confidence: 99%